Apolipoprotein CIII and N-terminal prohormone b-type natriuretic peptide as independent predictors for cardiovascular disease in type 2 diabetes. (July 2018) - Colombo, Marco; Looker, Helen C.; Farran, Bassam; Agakov, Felix; Brosnan, M.Julia; Welsh, Paul; Sattar, Naveed; Livingstone, Shona; Durrington, Paul N.; Betteridge, D.John; McKeigue, Paul M.; Colhoun, Helen M.
Abstract: Background and aims: Developing sparse panels of biomarkers for cardiovascular disease in type 2 diabetes would enable risk stratification for clinical decision making and selection into clinical trials. We examined the individual and joint performance of five candidate biomarkers for incident cardiovascular disease (CVD) in type 2 diabetes that an earlier discovery study had yielded. Methods: Apolipoprotein CIII (apoCIII), N-terminal prohormone B-type natriuretic peptide (NT-proBNP), high sensitivity Troponin T (hsTnT), Interleukin-6, and Interleukin-15 were measured in baseline serum samples from the Collaborative Atorvastatin Diabetes trial (CARDS) of atorvastatin versus placebo. Among 2105 persons with type 2 diabetes and median age of 62.9 years (range 39.2–77.3), there were 144 incident CVD (acute coronary heart disease or stroke) cases during the maximum 5-year follow up. We used Cox Proportional Hazards models to identify biomarkers associated with incident CVD and the area under the receiver operating characteristic curves (AUROC) to assess overall model prediction. Results: Three of the biomarkers were singly associated with incident CVD independently of other risk factors; NT-proBNP (Hazard Ratio per standardised unit 2.02, 95% Confidence Interval [CI] 1.63, 2.50), apoCIII (1.34, 95% CI 1.12, 1.60) and hsTnT (1.40, 95% CI 1.16, 1.69). When combined in a single model, only NT-proBNP and apoCIII were independent predictors of CVD, together increasing the AUROC using Framingham risk variables from 0.661 to 0.745. Conclusions: The biomarkers NT-proBNP and apoCIII substantially increment the prediction of CVD in type 2 diabetes beyond that obtained with the variables used in the Framingham risk score. Graphical abstract: Highlights: We measured five candidate biomarkers previously reported as associated with cardiovascular disease in type 2 diabetic patients. We assessed whether these biomarkers predict CVD on top of two sets of clinical covariates, both when considered singly and when combined. Models containing apoCIII and NT-proBNP increased prediction performance when compared to models containing only clinical covariates. Combined with NT-proBNP, apoCIII is useful in enriching CVD event rates in a sampling strategy for clinical trials in diabetes.